Effects of surgical factors on the outcomes of zygoma reduction malarplasty: a quantitative computed tomography study - Jong Chul Park (SpringerOpen, 2023)
Abstract Background Malarplasty is widely performed for zygoma reduction. The effects of body segmentation, plate bending, and postoperative arch location on zygomatic movement have not been analyzed using computed tomography (CT). Results We quantitatively analyzed the effects of surgical factors on zygomatic movements via superimposition of preoperative and postoperative CT images using three-dimensional software. Our results showed that segmentation had the most significant effect on the horizontal reduction of malar eminence (β = 0.593, r = 0.696, adjusted r 2 = 0.479, F = 79.595; p < 0.001). In addition, upward and posterior arch movements had significant effects on the anterior and posterior movements of the eminence (β = − 0.379 for vertical arch movement, β = 0.324 for arch setback, r = 0.603, adjusted r 2 = 0.352, F = 31.943; p < 0.001). The major factors that influenced inward arch movement at the coronoid process included segmentation and inward movement at the arch osteotomy site. To prevent interference of the coronoid process and arch, surgeons should pay attention to the degree of segmentation (β = 0.349) and inward movement at the arch osteotomy site (β = 0.494; r = 0.688, adjusted r 2 = 0.464, F = 50.412; p < 0.001). Conclusions Surgical factors related to malarplasty affect the movement of specific parts of the zygoma. In addition, accurate application is possible by considering the anatomical structure of the application area when using the bending plate.